The Effect of Integrated Marketing Communications Strategy on The Development Of Creative Economic Products In Moringa Processed MSMe Indra Jaya - Sudarso, Satrio; Sumartik (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
The discussion that forms the basis of the background of this research is the problem of developing creative economic products, especially on the MSME scale which is seen from the linkage of marketing communication strategies that have not been or have been implemented in one of the implementation of marketing activities for Processed moringa Indra Jaya. The purpose of this study was to determine and analyze the effect of advertising (X1), product packaging (X2), public relations (X3) and events marketing (X4) on product development (Y) in the context of the creative economy. The method used is a quantitative method. The population used is all consumers of Processed Moringa Indra Jaya. The sampling technique used is non-probability sampling in the form of random sampling of 100 people. Respondents were selected based on an existing database of MSME recommendations related to the respondent's domicile throughout Indonesia. Analysis techniques use multiple linear regression analysis and hypothesis testing using SPSS for Windows statistical tools. The results showed that all independent variables have a positive and significant effect on the dependent variable, partially or simultaneously.